ANALISIS PENINGKATAN MUTU PENDIDIKAN MELALUI GAMIFIKASI DALAM PROSES PEMBELAJARAN - Habibi, Muhammad Thoriq Zacky (Kelola: Journal of Islamic Education Management, 2025)
Education is a major pillar of national development, and its quality is determined by conventional curricula and teaching methods as well as innovative learning approaches. In recent years, the gamification of the integration of game elements into non-game contexts to enhance motivation, engagement, and learning outcomes has gained significant attention. This theory transforms education by using mechanisms such as rewards, challenges, and progress systems to mimic the dynamics of play in the classroom. gamification, based on theory and research, aims to encourage the intrinsic motivation of students and encourage active participation and deeper understanding. The purpose of this research is to analyze and explore how the implementation of gamification in educational institutions, to identify the shortcomings and advantages of the application of Gamification, to find out the problems of gemification in Indonesia. This research uses the method of library research, which is a method of gathering data by understanding and studying the theories from various literature related to this research.The results of this study show that gamification of education can improve student motivation, active participation in learning, and academic achievement. Gamification implementation requires good human resource integration, supporting infrastructure, and effective implementation. Gamification is regarded as an innovative method for improving student learning.